Meaningful perception of natural phenomenon associated with water in the poems of Ibn Zaydun and Ahmad Shawqi: a comparative study - Sheng, Du; Ismail, Muhd Zulkifli; Syed Abdullah, Syed Nurulakla; Wan Sulong, Wan Muhammad (Human Resource Management Academic Research Society, 2024)
The present study explores the importance of water as a natural phenomenon in the poetry of two prominent Arab poets, Ibn Zaydun and Ahmad Shawqi. Water, a vital element in both ecological and cultural contexts, serves as a rich metaphor for life, love, and transience in Arabic literature. This research highlights the significance of understanding how natural elements influence literary expression and cultural identity, particularly in the context of Arabic poetry. This comparative study employs a qualitative methodology textual analysis to examine selected poems from both poets, focusing on a close reading of selected poems from both poets. This approach allowed us to examine the imagery, themes, and stylistic choices related to water, revealing both shared elements and distinct perspectives. These perspectives are shaped by the unique historical contexts of Ibn Zaydun and Ahmad Shawqi, highlighting the influence of external factors on their artistic expression. Our results reveal that Ibn Zaydun often uses water to evoke feelings of longing and nostalgia, tying it closely to personal experiences and emotions. Meanwhile, Ahmad Shawqi portrays water as a powerful symbol of national identity and renewal, emphasizing its role in collective consciousness. Shawqi used the Nile and river streams frequently in his description of water, and he used the sea somewhat less than Ibn Zaydun. This contrast not only illuminates their artistic voices but also reflects the evolving relationship between nature and culture in Arabic poetry. This study paves the way for further research, particularly regarding the representation of other natural elements in Arabic literature and their cultural significance. A deeper investigation into regional variations in how water is depicted could provide valuable insights into the interplay between ecology and poetic expression in the Arab world, opening up new avenues for exploration and scholarly engagement.